Morphometric assessment of reflux oesophagitis in fibreoptic biopsy specimens. Issue 1 (January 1985) - Jarvis, L R; Dent, J; Whitehead, R
Abstract : The oesophageal epithelium of patients with reflux oesophagitis has been studied by means of computer aided morphometry. Measurements of histological features were made on biopsies from six cases before and after treatment. The size and elongation of the nuclei and their variation, the number of nuclei per unit length or per unit sectioned area, and the size and number of nucleoli per nucleus were measured for two zones of the epithelium, the base layer and the intermediate layer, which were independent of section orientation. The measurements were analysed using discriminant analysis. Significant discrimination was found between the two groups. The most important parameters were the number of intermediate layer nuclei per sectioned square millimetre, the mean intermediate layer nuclear area, and the number of nuclei per millimetre of base epithelium. These parameters are consistent with increased cell turnover of the non-ulcerated epithelium before treatment.